Collaborative Research Narratives in Counselling - Morsillo, Julie Elizabeth; Cocodia, Ebi A (International Journal of Research in Counseling and Education, 2024)
This paper examined the collaborative reflective process between the research supervisor and the student researcher. Using a descriptive analysis approach we found that this process can involve critically thinking through the personal or client narrative that the student may want to plan to explore in research, then acting on this plan with participants to find common community narratives, using reflective practices to develop into appropriate themes for critical discussion in the research findings.